Understanding Activation Patterns in Shared Circuits: Toward a Value Driven Model - Aziz-Zadeh, Lisa; Kilroy, Emily; Corcelli, Giorgio (Frontiers in Human Neuroscience, 2018)
Over the past decade many studies indicate that we utilize our own motor system to understand the actions of other people. This mirror system has been proposed to be involved in social cognition and motor learning. However, conflicting findings regarding the underlying mechanisms that drive these shared circuits make it difficult to decipher a common model of their function. Because previous theories do not satisfy interpretation of current literature findings, we propose adapting the “value-driven” model to explain discrepancies in the human mirror system literature. We will use this model to explain discrepant activation patterns in multiple shared circuits in the human data, such that a unified model may explain reported activation patterns from previous studies as a function of value.